Diamond nucleation on surface of C60 thin layers - 杨国伟 袁放成 刘大军 何金田 张兵临 (Science China. Mathematics, 1997)
Diamond nucleation on the surface of C60 thin layers and intermediate layer of Si substrates are studied by scanning electron microscopy (SEM). The cross-section SEM images of diamond films show that diamond grains really nucleate on the surface of C60 thin layers. The SEM images of diamond nucleating sites show the nucleating aggregation of diamond on C60 surfaces. The preferential oriented diamond films are observed. The plasma pre-treatment of C60 sublimating layers is a key factor for diamond nucleation.